Burkina Faso Rural Income Diagnostic - World Bank (Washington, DC, 2022)
With eight in ten of its people living in rural areas, Burkina Faso is one of the most rural countries in the world. Welfare has been improving for Burkina Faso’s rural households, but slowly, and faster income growth is needed for more robust progress. To determine how people in Burkina Faso’s rural areas can earn higher incomes, this diagnostic pursues two lines of inquiry. First, it analyzes the main constraints and opportunities for faster rural income growth. Then it identifies policy options to overcome select key constraints. The objective is to examine how those who currently live in rural areas, can earn higher incomes in the future. This report finds that supporting agricultural income growth requires addressing a policy bias and a market access gap. Together, these obstacles keep households focused on meeting their own food needs with their own production, rather than responding to market opportunities. This diagnostic highlights the importance of agricultural growth in raising rural incomes in Burkina Faso, particularly for poor households.